2019
DOI: 10.3390/foods8100430
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lactobacillus acidophilus, Oenococcus oeni, and Lactobacillus brevis on Composition of Bog Bilberry Juice

Abstract: This study investigated the impact of Lactobacillus acidophilus NCFM, Oenococcus oeni Viniflora® Oenos and Lactobacillus brevis CICC 6239 on bog bilberry juice with a considerably low pH and rich in anthocyanins content. Moreover, the effects of the strains on the composition of phenolic compounds, amino acids, ammonium ion, biogenic amines, reduced sugars, organic acids, and color parameters of the juice were studied. All three bacteria consumed sugars and amino acids but exhibited different growth pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 62 publications
(80 reference statements)
2
7
0
Order By: Relevance
“…The L. plantarum C8‐1 strain in the original pH juice (pH 2.67) displayed a continuous growth decrease during the entire process, resulting in a significantly lower strain growth than at the beginning (Figure 1). This was consistent with the growth of Lactobacillus acidophilus at the original pH level but differed from Lactobacillus brevis and Oenococcus oeni , as was evident from our previous study (Chen et al., 2019). The L. plantarum C8‐1 strain in the pH‐adjusted juice (pH 3.60) showed no significant growth increase during the first 3 days but increased slightly from 3 to 7 days (Figure 1).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The L. plantarum C8‐1 strain in the original pH juice (pH 2.67) displayed a continuous growth decrease during the entire process, resulting in a significantly lower strain growth than at the beginning (Figure 1). This was consistent with the growth of Lactobacillus acidophilus at the original pH level but differed from Lactobacillus brevis and Oenococcus oeni , as was evident from our previous study (Chen et al., 2019). The L. plantarum C8‐1 strain in the pH‐adjusted juice (pH 3.60) showed no significant growth increase during the first 3 days but increased slightly from 3 to 7 days (Figure 1).…”
Section: Resultssupporting
confidence: 91%
“…Unlike other fruit juices, bog bilberry contains high organic acid levels, resulting in a juice with extremely low pH conditions (Wei et al., 2014). The impact of Lactobacillus acidophilus , Oenococcus oeni , L. brevis , and L. plantarum on bog bilberry juice has previously been investigated (Chen et al., 2019; Wei et al., 2018). It was found that (1) although low pH levels (<3.0) limited the growth and metabolism of bacteria, they still affected the chemical composition of the bog bilberry juice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past years, there has been a growing interest to develop new functional food products. The consumption of fermented beverages is a worldwide trend because of their health-promoting effects and associated properties [1,2,3,4,5,6,7]. Fermented beverages could contain probiotic microorganisms, which are living microorganisms that when administered in adequate amounts in edible matrices confer health benefits on the consumers [2,8,9,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Among the production processes, lactic acid fermentation is considered as a simple and valuable biotechnology for enhancing those features of fruits (Di Cagno et al., 2013; Swain et al., 2014; Szutowska, 2020). In this regard, the effect of lactic acid fermentation on the texture, color, and composition of many kinds of fruits has been well studied (Di Cagno et al., 2011; Chen et al., 2019; Chen, Ouyang, et al., 2019; Filannino et al., 2013; Li et al., 2021; Muhialdin et al., 2020, 2021; Peng et al., 2021; Ricci et al., 2018; Wei et al., 2018). However, the literatures concerning the lactic acid fermentation of goji berry fruits are scarce (Liu et al., 2019).…”
Section: Introductionmentioning
confidence: 99%